ANALISIS KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH DIDINAS PENGELOLAAN KEUANGAN DAN ASET KABUPATEN ROKAN HULU - PURNAMASARI, RESTU YULIZA (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
Analisis Kontribusi Pajak Daerah Terhadap Pendapatan Asli DaerahDi Dinas Pengelolaan Keuangan Dan Asaet Kabupaten Rokan HuluAndi Afrizal, SE.M.Si,AK,CA 1), Hamdi Sri Maryoni, M.Ec.Dev2), Restu Yuliza Purnamasari3)andiaprizal7@yahoo.co.idhamdiYoni@yahoo.co.idrestuyulizapurnamas@gmail.comABSTRACTThis study aimed to analyze Contributions Against Local Tax Local Revenue at the Department of Finance and Asset Management in Rokan Hulu, during the timeframe of five (5) years from 2010-2014. Types and sources of data collected primary data, secondary data, research was conducted in the Department of Finance and Asset Management which is located in the District Government Offices Complex Pasir Pengaraian Rokan Hulu. Data collection techniques used were interviews, documentation and keperpustakaan. Data analysis techniques using quantitative descriptive method. Results were obtained that the amount of the contribution of local taxes to predict an increase in local revenues at the Department of Finance and Asset Management Rokan Hulu can be calculated using the formula with the research contribution of local taxes to local revenues during the five (5) years from 2010-2014 amounting to 27.17%. This means that the better the local tax revenue, there is a tendency that will increase revenue. The suggestions in this study specifically on the Department of Finance and Asset Management Rokan Hulu in order to further optimize the local tax explore all the potential of existing taxes in Rokan Hulu in order to increase local revenue, the leader must provide and foster technical capabilities in the field digging potensi- the potential that exists.